Influence of gate leakage current induced shot noise on the Minimum Noise Figure of InAlAs/InGaAs double-gate HEMT. (September 2017) - Bhattacharya, Monika; Jogi, Jyotika; Gupta, R.S.; Gupta, Mridula
Abstract: In this paper, the influence of hot electron injection induced gate leakage current on the noise performance of InAlAs/InGaAs double-gate HEMT has been studied following a comprehensive analytical approach. The presence of two gates on both sides of the channel in a double-gate HEMT not only provides significant improvement in its ultra-high speed and noise performance, but is also responsible for higher gate leakage current which becomes very dominant in high field conditions. Therefore, in order to explore the reliability and potential of this device under high gate and drain bias conditions, a thorough investigation of the effect of gate leakage current induced shot noise gate current on the Minimum Noise Figure of the device has been carried out. Highlights: Evaluation and assessment of shot noise generation in InAlAs/InGaAs double-gate HEMT. Comparison of the effect of gate leakage current induced shot noise on the performance of single-gate and double-gate HEMT. Exploration of potential and reliability of the device under high gate and drain bias conditions.